Optimization Of process parameters for microbial cellulose production from rice-washing wastewater (NATA-DE-LERI) By Acetobacter Xylinum - Alwani Hamad; Giswantara Giswantara; Endar Pusapawiningtyas; Regawa Bayu Pamungkas; Abdul Haris Mulyadi (Universitas Muhammadiyah Purwokerto, 2023)
Nata is a bacterial cellulose obtained from the fermentation of Acetobacter xylinum. It is often found in desserts as a health supplement because of its high fiber content. It is not only produced from coconut water, known as nata-de-coco but can also be produced from other sources, such as wastewater from rice washing, called nata-de-leri. This study aimed to optimize the parameters of bacterial cellulose (nata-de-leri) fermentation by statistical methods to improve production. First, the Placket-Burman Screening Design was applied to address the essential parameter components affecting nata-de-leri production. Eight factors are continuously checked, and unimportant elements are removed to obtain a smaller, more manageable set of characteristics. Second, a feedback surface method using Central Composite Design (CCD) was used to determine the optimal level of fermentation parameters using yield response. The results of this study show that sucrose concentration, CO(NH2)2 concentration, inoculum concentration and fermentation time are believed to be the main factors for nata production. The estimated optimal values nata-de-leri production when using 500 ml of rince washing wastewater are as follows: sucrose is 17.5 g; CO(NH2)2 is 12 g; volume of starter is 60 ml; fermentation time for 12 days. This results in a yield of 97.20%. From this study, the optimum yield in nata-de-leri is 20% larger than the baseline parameters